Effects of Age and Dietary Factors on the Blood Beta-Hydroxybutyric Acid, Metabolites, Immunoglobulins, and Hormones of Goats - Abdelsattar, Mahmoud M.; Vargas-Bello-Pérez, Einar; Zhuang, Yimin; Fu, Yuze; Zhang, Naifeng (Frontiers in Veterinary Science, 2022)
The study was aimed to determine how blood beta-hydroxybutyric acid (BHBA) and blood health indicators are affected by age and dietary BHBA in goat kids. Thirty male goats of five ages (1, 2, 3, 6, and 12 months (m) old) were selected for blood sampling. Another sixty-four goat kids (half males and half females) were weaned at 1 m old and fed starter diets with control, low, medium, and high BHBA doses (0, 3, 6, and 9 g/animal/d, respectively). There were significant effects (P < 0.01) of ages on the blood parameters of goat kids. The 6 and 12 m old kids had lower blood total protein, globulin, BHBA, and IgA, IgM concentrations, but higher albumin to globulin ratio compared with younger goats. The blood glucose decreased, but the IgG increased over time. In blood, growth hormone (GH) and insulin-like growth factor I (IGF-I) were the lowest (P < 0.05) at 3 m and the highest (P < 0.05) at 12 m old. The high dietary BHBA improved (P < 0.05) the ratio of albumin to globulin of 2 m old kids compared with control. The blood GH and IGF-I were lower (P < 0.01) in the medium BHBA dose at 2 m of age than control. These results suggested that age greatly impacted blood composition, especially around weaning, and dietary BHBA showed beneficial regulating effects on blood total protein level in young goats.